Electrophysiological Effect of Kooshmanda Swarasa Ghrita in Right Central Parietal Epilepsy in a Child on Anti-Epileptic Drug (AYUSHDHARA, 2025)
Seizures are abnormal excessive neuronal activity in the brain and is a major indicator of an underlying brain pathology. This is termed as epilepsy, if the brain has a predisposition to generate these seizures leading to further neurobiological and cognitive consequences. The effects of each seizure activity vary depending on its type, area of brain involved and the pathogenesis. Incidence of seizures is high in childhood and this itself reflects the variety of underlying brain disorders.  This in turn may be associated with comorbidities of varying extent. This can range from minor learning disabilities to intellectual disability and even more severe complications like deterioration in gait, movement disorders, sleep and intestinal disorders. 60% of these seizures respond to management and the remaining 40% remain refractory or intractable. This is a case study of a child with focal epilepsy on anti-epileptic drug managed with Kooshmanda swarasa ghrita for a period of 90 days. The child was assessed before and after study with Hague Seizure Severity Scale, frequency of seizure, electroencephalogram and quality of life in childhood epilepsy. The results showed a considerable improvement is the scores.